Changing HCV patient profiles: insights from a large multinational real-world sofosbuvir/velpatasvir (SOF/VEL) dataset. (March 2023) - Mangia, A.; Fagiuoli, S.; Di Marco, V.; Shafran, S.; Khalili, M.; Milligan, S.; Papatheodoridis, G.; Ouzan, D.; Rosati, S.; Ramji, A.; Teti, E.; Garcia-Retortillo, M.; et al.
Abstract : Background and aims: The profile of HCV patients being started on direct-acting antivirals (DAAs) has shifted towards more vulnerable populations. This large real-world analysis describes the diverse profile of these populations according to age and sex. Method: Adult HCV patients from 37 clinical cohorts across nine Countries treated with SOF/VEL for 12 weeks without ribavirin were included. Those with a history of decompensation or prior NS5A-inhibitor exposure were excluded. Patients' characteristics, time to treatment, and sustained virological response ≥12 weeks after end of treatment (SVR), stratified by age and sex, were analyzed. Results: Among 6356 patients, 2274 were aged <50 y, 2568 50−65 y, and 1514 > 65 y. Within these age strata, 73%, 65%, and 45%, respectively, were male. Vulnerable populations were well represented, and ∼20% of all patients had a history of IV drug use. Male patients were more likely to have compensated cirrhosis and to be infected with HCV genotype 3. Significantly fewer mental health disorders were seen in male patients. However, use of antipsychotics appeared similar, irrespective of sex. Median TT was shorter in male patients across the age spectrum. In 5845 patients with a valid result, SVR was high across age ranges, with no significant differences observed between males and females (<50 y: female 98.7%, male 99.2%; 50−65 y: female 98.7%, male 98.1%; >65 y: female 99.3%, male 98.3%). 475 pts did not achieve SVR for a non-virological reason: mostly loss to follow-up, with no differences between males and females across age strata. Conclusion: SOF/VEL shows high cure rates across different age and sex groups. Antipsychotic drug use appeared similar in males and females, despite significantly fewer mental health disorders in male pts. TT varied from 1 day to >6 months and was shorter in males.